Analisis Software Dukungan Pengambilan Keputusan : Vanguard Busines Analytics - Toni Kusnandar (STMIK Mardira Indonesia, Bandung, 2018)
Decision Support System is necessary for decision makers at every level of management. Diverse information needs to be well organized and compiled so that decision makers can make decisions appropriately.The ready-to-use DSS software to be analyzed is a Vanguard Busines Analytics Suite that combines Decision Analysis, Time-Series Forecasting, Monte Carlo Simulations, and Optimization into integrated packages. This software allows us to apply decision analysis techniques throughout our organization to problems ranging from simple projects to enterprise strategic plans.The Vanguard system is a comprehensive business solution to improve the quality, reliability and speed of management decisions. This is done by helping us collaborate with peers on important plans, analyzing alternatives using simulations and modeling techniques, automating routine decisions using expert system technology, and increasing overall management effectiveness by adding structures to chaotic processes normally. Keyword : decision support system.